Framing of Political Leaders During the #BringBackOurGirls Campaign by the Nigerian Press: A Comparative Study of Guardian and Vanguard Newspapers - Akpojivi, Ufuoma; Aiseng, Kealeboga (Frontiers in Communication, 2022)
This study examines Nigeria's political leaders' framing during the #BringBackOurGirls movement using two selected national newspapers in Nigeria, i.e. the Guardian and the Vanguard newspapers. Using 46 news stories culled during the periods of April 14, 2014, to June 14, 2014, and May 29, 2015, to July 29, 2015, which represent two significant eras, i.e. when the schoolgirls were abducted, and when there was a change in government, the study argued that four frames of government failure, the desperation of citizens, politicization of government actions and heroism were dominant in both presses reportage. During the first period of study, both presses were critical of President Goodluck Jonathan and his inability to secure the release of the abducted Chibok schoolgirl as they used frames of “liar”, “clueless”, and “failure” amongst others to characterize his government actions and inactions. However, during the second study period, both presses were less critical of President Buhari as they ascribed the “hero” frame to him due to his vast military experience. Nevertheless, the ideological position of both newspapers influenced their reportage as Guardian news stories provided depth analysis, while Vanguard newspaper stories lacked depth.